Sedimentation from buoyant muddy plumes in the presence of interface mixing: An experimental study. Issue 4 (1st April 2017) - Rouhnia, Mohamad; Strom, Kyle
Abstract: A series of flume experiments were conducted to study the sediment removal rates, characterized by an effective settling velocity, from buoyant muddy plumes overriding clear saltwater at steady state conditions under different Richardson numbers and initial suspended sediment concentrations. The experiments were all carried out in the subcritical regime, leading to cusps style instabilities at the interface of the two fluids. Flocculation in the experiments was not suppressed, yet flocs remained small while in the plume layer. Data from the experiments allowed for calculation of the individual floc settling velocity, W s, f, and the overall effective settling velocity, W s, e f f, i.e., that velocity needed to predict the downward flux with C W s, e f f . Results showed that W s, e f f was greater than the floc settling velocity in all runs. W s, e f f was found to increase with plume velocity and interface mixing but not with plume concentration. The difference between the effective and floc settling velocities was therefore attributed to turbulent diffusion brought on by mixing at the interface and not to convective sedimentation or leaking. The turbulence enhanced settling velocity, W s, t, was found to be a strong function of the Richardson number, and conceptual and empirical equations are presented to predict W s, t as a function of the plume surface velocity, Ups, and Richardson number, Ri ; this analysis showed that W s, t ∝ U p s R i − 2 . In the runs with low Richardson number, W s, t was approximately equal to the floc settling velocity, leading to an overall doubling of the effective settling velocity relative to that of the individual particles. Key Points: Measurements of vertical sediment flux from buoyant muddy plumes were made Density anomaly and convective sedimentation did not occur for subcritical plumes Turbulent sediment fluxes were related to the average Richardson number